INDONESIAN EFL TEACHERS’ TRAINING NEEDS AND PERCEPTIONS OF CONTEMPORARY ELT APPROACHES - Erika Nur Shafiyah; Asep Suparman; Mohammad Soni (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyze English teachers’ experiences in participating in in-service training and identify their training needs related to contemporary English language learnng approaches. Teacher professional development is a crucial factor in improving the quality of learning, particulary in facing the 21st century, which emphasizes learning using communicative, collaborative approaches, and the use of technology in the teaching and learning process. This study employed a quantitative approach with a survey method and involved English teachers as research respondents. Research data were collected using a questionnaire designed to obtain information related to teacher training experiences, training providers, training needs, and teachers’ level of knowledge regarding various contemporary English language learning approaches. The obtained data were tan analyzed descriptively to describe the training conditions and teachers’ profesional development needs. The results of this study indicate that English teachers’ participation in training is still relatively limited, even though the training is organized by various institutions, In addition, teachers alo demonstrated a high need for training on contemporary learning approaches, paticularly those related to the use of technology in English language learnig. The findings of this study indicate that teachers have a fairly good level of knowledge of several approaches, such as Project-Based learning, Student-Centered Approach, Task-Based Language teachng, although their understanding of technology-based approaches is still relatively low. Therefore, this study emphasizes the importance of providing more systematic, sustainable, and relevant teacher training programs that are aligned with learning needs.